Design and development of phoneme based sign language recognition system for the hearing impaired - Palaniappan, Rajkumar (School of Mechatronic Engineering, 2012)
This thesis discusses the development of a Phoneme based sign language recognition system for the hearing impaired. Previous research on sign language recognition systems have concentrated on finger spellings recognition or isolated word recognition. This research focuses on developing a sign language recognition system for recognizing 44 English phonemes.